Implementation of a frequency control in a biomass gasifier system - Yecid Muñoz; Adalberto Ospino; Carlos Robles; Carlos Arizmendi (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Distributed power generation has grown in popularity in recent years, especially in areas not connected to the national grid. As a result, rural microgrids are becoming more common, involving great potential for energy based on biomass conversion such as gasification. After analyzing distributed power generation facilities in developing countries, the authors found problems with the frequency stability. This paper focuses on solving the problem of frequency control in energy supplied by microgrids based in biomass gasification. For that purpose, the authors have developed a physical model of a downdraft gasifier, this model was used for design a novel strategy for frequency control, which has been based and validated on an existing gasification system, which supplies power to a population in Necoclí (Colombia).